Exercise Echocardiography in Uncomplicated Type 2 Diabetic Patients: which Parameters are Useful? - Schuster, Iris; Maufrais, Claire; Krastevich, Monika; Doucende, Gregory; Perez-Martin, Antonia; Jourdan, Nathalie; Demattei, Christophe; Nottin, Stéphane (Cardiology and Cardiovascular Medicine, 2022)
Background: The aim of this study was to (1) identify the most sensitive and clinically relevant echocardiographic variables in order to detect early Left Ventricular (LV) dysfunction in uncomplicated Type 2 Diabetic Patients (T2D) in comparison with Sedentary (SC) and Trained Controls (TC), at rest and during exercise, and (2) to understand the mechanisms of exercise intolerance in these patients. Methods: 20 T2D without micro- or macrovascular complications and without any other uncontrolled risk factor, 20 SC, and 20 TC were studied at rest and during a cardiopulmonary exercise test using conventional, tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE) including twist-untwist mechanics analysis. Results: LV dysfunction was detectable in T2D by resting echocardiography. During exercise, T2D had the lowest LV diastolic and systolic functional reserve and the most limited vasodilation compared to SC and to TC who showed the highest adaptability. Exercise STE twist-untwist analysis showed lower feasibility and higher variability in T2D compared to SC and TC. T2D patients had lower longitudinal strain and higher untwist/twist ratio compared to SC but not in comparison to TC. Conclusion: Conventional and TDI data were the most robust echocardiographic parameters, showing early LV dysfunction and evidencing the contribution of diastolic and systolic dysfunction to exercise intolerance with the expected pathophysiological continuum between groups. Exercise STE data, which showed low feasibility and high variability in T2D, did not exhibit the expected distribution between groups, underlining the fact that strain adaptations in different pathophysiological situations need further explorations.